α‑Methylstilbene Isomers: Relationship of Structure to Photophysics and Photochemistry - Krishnan, Sumesh B.; Clark, Ronald J.; Lin, Xinsong; Dmitrenko, Olga; Hilinski, Edwin F.; Kuhn, Leah R.; Alabugin, Igor V.; Saltiel, Jack (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2022)
Significant differences in the photochemical and photophysical behavior of trans-α-methylstilbene and trans-stilbene have been attributed to structural changes caused by the steric requirements of the methyl group. We present here the X-ray structures of cis- and trans-α-methylstilbene (c- and t-MeSt). This is the first X-ray structure of a cis-stilbene. Despite the pronounced departure from phenyl group coplanarity, the solid-state packing of t-MeSt resembles that of trans-stilbene in that both exhibit disorder with a bicycle pedal structural relationship, dynamic in t-St but static in t-MeSt. We compare the X-ray structures with calculated structures. We also compare our steady state and transient photochemical and spectroscopic results with predictions in a recent theoretical paper that anticipated some of our experiments. Deviations from planarity imposed by the methyl substitution account for the shorter lifetimes of the trans excited states. The rapid torsional relaxation of 1 t-MeSt* to the twisted intermediate 1p*, k tp = 2.9 × 1012 s–1, observed using fs transient absorption spectroscopy, explains the sharp decrease in the fluorescence quantum yield of t-MeSt. We correct misconceptions that have appeared in the literature concerning the shape of the stilbene potential energy surface in S 1. The nonplanarity due to methyl substitution leads to chirality issues that are relevant in biological molecules such as the protonated Schiff bases of retinal in the opsins.